Firing of Limestone in JPN Pilot Plant - Chee, Hoong Phang; Jalal, Abdullah Aziz; Norashid, Aziz (Penerbit Universiti Sains Malaysia, 2004)
Limestone is a natural occurring mineral throughout the world. It is widely used in the cement manufacturing, construction and building, metal refining processes, quicklime industries, agricultural industries, flue gases treatments, etc. The chemical composition of the limestone varies from one region to the other region, but it mainly consists of calcium carbonate. In the Peninsular Malaysia, 7 billion tonnes reserve of limestone has been identified by the Geological Survey Department, Malaysia. It is found that 55% of the limestone in Peninsular Malaysia contains 95% calcium carbonate (Sulaiman, 1996). It is feasible to be used as raw materials to produce quicklime.